Investment decision in generation y - Simanjuntak, Sri Ida Royani; Sitorus, Sunday Ade; Hasugian, Christnova (Institute of Computer Science (IOCS), 2024)
This research aims to examine the influence of financial literacy and emotional intelligence on investment decisions. This type of research is quantitative research. The data processed is primary data obtained from the results of distributing questionnaires using techniques purposive sampling to the millennial generation who live in the city of Medan. The research sample consisted of 101 respondents. Data analysis was carried out using the PLS (Partial Least Square) program. The results of this research show that there is a positive and significant influence of financial literacy and emotional intelligence on investment decisions. Financial literacy and emotional intelligence must continue to be improved so that the millennial generation is increasingly motivated to invest so that in the future they will have good finances